THE CONSTRUCTION OF THE VICE PRESIDENT'S AUTHORITY IN INDONESIA'S STATEMENT SYSTEM - Widayati Widayati; Sri Kusriyah; Winanto Winanto (Jurnal Pembaharuan Hukum, 2022)
The 1945 Constitution of the Republic of Indonesia stipulates that the President and Vice President are directly elected by the people. The position of the Vice President is at the level below the President. The authority of the Vice President is not clearly and unambiguously regulated in the 1945 Constitution of the Republic of Indonesia or in the laws and regulations below it. As an assistant to the President, the authority of the Vice President is highly dependent on the President. The Vice President's authority will only appear when the President is absent. The authority of the Vice President in Indonesia's constitutional history varies from one to another. For the division of authority between the President and the Vice President, as well as clarity on the authority of the Vice President, it is necessary to have a law regulating the presidential institution. The law on the presidential institution will later serve as the legal basis for the President to share authority with the Vice President. With the division of authority, there will be clarity as to what is the authority of the Vice President, so that when a problem occurs, it can be resolved quickly and thoroughly, without throwing responsibilities at each other. The clarity of the division of authority will also greatly assist the DPR in carrying out its supervisory function, and for the public to assess the performance of the Vice President.